Risk factors of pediatric urinary tract infections: an epidemiologic study - Esteghamati, Maryam; Mousavi, Seyedeh Elaheh; Alizadeh, Shervin Haj (International Journal of Contemporary Pediatrics, 2018)
Background: Urinary tract infection (UTI) is the second most prevalent pediatric infection, and if it is not recognized and treated properly, it can cause severe irreversible complications such as renal failure and hypertension. In this research, some of the risk factors of UTIs were compared in children with urinary tract infections. Methods: This is a cross-sectional study, with the urinary tract infection as the dependent variable and gender, circumcision status, history of urinary catheterization, family history, history of renal stone, hypercalciuria, constipation history, reflux, neurogenic bladder, phimosis, posterior urethral valves (PUV), ureteropelvic junction obstruction (UPJO), and ureterovesical junction obstruction (UVJO) as the independent variables. A total of 405 children were studied in this research. The data was collected using questionnaires, checklists, and examinations. Data analysis was also carried out using descriptive and analytical statistics method in SPSS. Results: This research revealed the prevalence of urinary tract infection among children with several risk factors, and the common factors were positive family history, history of urinary catheterization, constipation, and other non-anatomical disorders (history of renal stone and hypercalciuria. The most common risk factors regardless of gender and age were non-anatomic disorders that were observed in 147 cases (43.7%) (p-value<0.001). Among the non-anatomical factors, constipation was the most common factor observed in 66 cases (16.3%). A higher rate of urinary infection was observed in the uncircumcised male patients than the circumcised patients, and there was a significant relationship between circumcision and UTI. Conclusions: In this study, urinary tract infection staged a significant relationship with gender, circumcision status, urinary catheterization history, family history, renal stone history, hypercalciuria, history of constipation, reflux, neurogenic bladder, phimosis, PUV, UPJO, and UVJO.